THE IMPLEMENTATION OF COMMUNICATIVE APPROACH IN TEACHING ENGLISH AT JUNIOR HIGH SCHOOL - Jamaliah Jamaliah; Fauziah Fauziah; Farizawati Farizawati (Proceedings of ISELT FBS Universitas Negeri Padang, 2017)
This study was intended to obtain the information on the teachers’ understanding of Communicative Approach principles and the way of the teachers’ implementation of the principles in teaching English. The subjects of this study were eighteen English teachers at four Junior High Schools in Sigli, Aceh. The data were collected from multiple sources such as observation, questionnaires and documents. Table of frequency and percentage were used to analyze the data that had been grouped and classified based on the research problems. Finding shows that most of English teachers (88,8%) have understood about Communicative Approach principles. They got the information about the principles from The 1994 Curriculum, related books, in-service training and from the articles of education. And most of them (77.7 % ) also implemented Communicative Approach principles in teaching English at Junior High Schools in Sigli through some activities such as games, describe and draw, role play, questions and answers, simple dialogues and problem solving. Fourteen of respondents (77.7%) agree that Communicative Approach is still suitable to use in teaching English even though curriculum is changed. Because this teaching method can develop four language skills and language components such as vocabulary, pronunciation, and grammar as suggested. It was not only appropriate to the 1994 Curriculum and the 2004 Curriculum but also appropriate to the 2013 Indonesian National Curriculum. All of the respondents used textbooks that provided communicative tasks in presenting the material of teaching. Most of the respondents helped and appreciated the students in any way in learning to produce good utterances.